2018
DOI: 10.3390/nu10121871
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous miRNA and mRNA Transcriptome Profiling of Differentiating Equine Satellite Cells Treated with Gamma-Oryzanol and Exposed to Hydrogen Peroxide

Abstract: Gamma-oryzanol (GO) is a popular supplement for performance horses, dogs, and humans. Previous studies indicated that GO supplementation decreases creatine kinase activity and lactate level after exercise and may affect oxidative stress in Thoroughbred horses. GO may change genes expression in equine satellite cells (ESC). The purpose of this study was to evaluate the effect of GO on miRNA, gene expression, oxidative stress, and cell damage and viability in differentiating ESC pretreated with hydrogen peroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
1
1
0
1
Order By: Relevance
“…Furthermore, H 2 O 2 accumulation has been noted in equine sports and diseases, accompanied by cell apoptosis and mitochondrial dysfunction ( Kirschvink et al, 2008 ; Goncalves et al, 2015 ; Ji et al, 2016 ). Our results demonstrated that ESMCs exposed to H 2 O 2 showed elevated oxidative stress, decreased antioxidant capacity, and disrupted cellular energy metabolism, consistent with previous reports ( Chodkowska et al, 2018a ; b ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, H 2 O 2 accumulation has been noted in equine sports and diseases, accompanied by cell apoptosis and mitochondrial dysfunction ( Kirschvink et al, 2008 ; Goncalves et al, 2015 ; Ji et al, 2016 ). Our results demonstrated that ESMCs exposed to H 2 O 2 showed elevated oxidative stress, decreased antioxidant capacity, and disrupted cellular energy metabolism, consistent with previous reports ( Chodkowska et al, 2018a ; b ).…”
Section: Discussionsupporting
confidence: 93%
“…However, CON and FLAX remained elevated at 30 min post-exercise on d 0, 30, and 60. This could be explained by RICE containing γ-oryzanol, a mixture of ferulic acid esters that has been shown to decrease lactic acid concentrations after exercise [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…W oparciu o wyniki badań wykorzystujących komórki tkanki mięśniowej poprzecznie prążkowanej, pobranej od młodego konia, ustalono również, że gamma-oryzanol przyspiesza możliwości regeneracyjne. Wzrost szybkości odbudowy mięśni po wysiłku fizycznym skorelowany jest ze wspomaganiem aktywności komórek satelitarnych niezbędnych dla prawidłowego procesu odbudowy włókien mięśniowych uszkadzanych podczas intensywnego treningu [49].…”
Section: Aktywność Biologiczna Wynikająca Z Potencjału Przeciwutleniającego Gamma-oryzanoluunclassified